Zero meridian - Rivera, Alex C.; Wake Up Films Production Ltd.; FeelSales (Firm) ([Kingston upon Thames (London, England)] : Wake Up Films Production, 2017)
The constant struggle to live a normal life and control the intense desire to consume is the hell of these testimonies that tell in first person the great undesirable effect they suffer day by day due to their addiction to drugs.--
Originally released as a motion picture in 2017.
Cinematographer and editor, Alex C. Rivera ; music, Max McGuire, Alastair Adams, Sascha Blank.
In Spanish; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed September 27, 2019)
Keywords: Drug addicts -- Spain -- Interviews; Drug abuse -- Spain; Documentary films; Nonfiction films; Internet videos; Streaming video